Analisis Pendapatan Usaha Ternak Sapi Potong Hasil Inseminasi Buatan di Kabupaten Tapanuli Selatan - Budi Sakti, Anto Dohar; Hasnudi, Hasnudi; Kardhinata, E. Harso; Hasibuan, Syahbudin (Universitas Medan Area, 2019)
The purpose of this research is to know the difference of income of artificial insemination and non artificial insemination beef cattle ranchers, and also to know the influence of cow number, feed price, medic price, labor wage, artificial insemination cost, depreciation cost and equipment cost to beef cattle farmer income. The data used are primary data, the sample are 99 respondents of beef cattle ranchers in South Tapanuli Regency. This research used test of mean and doubled linear regression at significance level 95%. This study has shown that independent variables together and partially affect the dependent variable. The result of hypothesis test proves for artificial insemination breeder that the variable of cow number, feed price and artificial insemination cost have positive effect, drug price variable, labor wage, depreciation cost and equipment cost have negative effect to beef cattle rancher income. Meanwhile, for non-artificial insemination farmers that the variable of cattle, feed price and labor wage have positive effect, drug price variable, depreciation cost and equipment cost negate to beef cattle farmer income